ChemInform Abstract: Scaffold Diversity Synthesis and Its Application in Probe and Drug Discovery. Issue 35 (August 2016) - Garcia‐Castro, Miguel; Zimmermann, Stefan; Sankar, Muthukumar G.; Kumar, Kamal
Abstract: Review: [recent developments towards the construction of compound libraries and their application in drug and probe discovery; 86 refs.